Strategi Teknik “Bite & Step” untuk Meningkatkan Keterampilan Sosial Anak Berkebutuhan Khusus di Sekolah - Markus Nanang Irawan (Universitas Semarang, 2020)
When interacting with others, each person certainly needs a good skill in communication so that the purpose of socializing at school goes smoothly and is achieved. But for student with special needs seems difficult to achieve because they have obstacles or problems in communication. Therefore we need a treatment or assistance called social skills training. The purpose of the study was to determine the effectiveness of the strategy of a game technique called